2020
DOI: 10.1002/anie.202003635
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐Based Prediction of Promiscuous Acyltransferase Activity in Hydrolases

Abstract: Certain hydrolases preferentially catalyze acyl transfer over hydrolysis in an aqueous environment. However, the molecular and structural reasons for this phenomenon are still unclear.H erein, we provide evidence that acyltransferase activity in esterases highly correlates with the hydrophobicity of the substrate-binding pocket. Ah ydrophobicity scoring system developed in this work allows accurate prediction of promiscuous acyltransferase activity solely from the amino acid sequence of the cap domain. This co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 37 publications
2
77
0
9
Order By: Relevance
“…Other phosphatases behave similarly (Han & Coleman, 1995;Tasnádi et al, 2020;van Herk, Hartog, van der Burg & Wever, 2005). Similar behavior has been noted for select esterases/lipases and proteases/N-acylases (Adlercreutz, 2017;Marsden et al, 2020;Müller et al, 2020). Extending previous studies, notably those on amidases and acyltransferases (Gololobov et al, 1988(Gololobov et al, , 1990Youshko et al, 2002), the kinetic framework analysis reported here could be useful in the study of these enzymes and group-transfer reactions catalyzed by them.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Other phosphatases behave similarly (Han & Coleman, 1995;Tasnádi et al, 2020;van Herk, Hartog, van der Burg & Wever, 2005). Similar behavior has been noted for select esterases/lipases and proteases/N-acylases (Adlercreutz, 2017;Marsden et al, 2020;Müller et al, 2020). Extending previous studies, notably those on amidases and acyltransferases (Gololobov et al, 1988(Gololobov et al, , 1990Youshko et al, 2002), the kinetic framework analysis reported here could be useful in the study of these enzymes and group-transfer reactions catalyzed by them.…”
Section: Discussionsupporting
confidence: 77%
“…Many enzymes in enzyme class 3 (hydrolases) catalyze chemical group transfer to acceptors (e.g., alcohols) other than water. Such donor-toacceptor transfer reactions are the basis for important applications of hydrolytic enzymes in organic synthesis (Adlercreutz, 2017;Giordano, Ribeiro, & Giordano, 2006;Kasche, 1986;Marsden, Mestrom, McMillan, & Hanefeld, 2020;Müller et al, 2020;Seibel, Jördening, & Buchholz, 2006;Vera, Guerrero, Aburto, Cordova, & Illanes, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray technique is useful to understand chemical and biological processes and the functions of various target molecules [2]. The obtained structural information provides insight into the development of new drugs, and it enables protein engineering, which can develop proteins with various industrial applications [2][3][4][5]. Hence, the traditional X-ray crystallography research technique has significantly contributed to the development in the field of academics, medicine, and various other industries.…”
mentioning
confidence: 99%
“…[5][6][7] Kürzlich konnten wir jedoch zeigen, dass viele Esterasen aus der Familie der bakteriellen hormonsensitiven Lipasen (bHSL) ebenfalls promiskuitive Acyltransferase-Aktivität aufweisen. [8] Manche dieser Enzyme sind hinsichtlich ihrer Effizienz vergleichbar mit MsAcT, was darauf hindeutet, dass dieses Phänomen weiter verbreitet ist, als bisher angenommen. Die enzymatische Produkthydrolyse sowie die geringe Übertragungseffizienz der Acylgruppe stellen dabei Nachteile im Hinblick auf eine Anwendung im industriellen Maßstab dar.…”
unclassified
“…Dies ist das zugrundeliegende Prinzip des kürzlich verçffentlichten pNP-AcT-Assays. [8] Im Falle von EstCE1 konnten wir einen achtfachen Anstieg der scheinbaren pNPA-Hydrolyserate bei nur 6,3 % (v/v) Methanol beobachten (Abbildung S1). Um zu zeigen, dass die beschleunigte Freisetzung von pNP ein Resultat der Umesterung zu Methanol ist, wurde die EstCE1-katalysierte Bildung von Methylbutyrat aus pNP-Butyrat und Methanol durch Gas-Chromatographie-Massenspektrometrie (GC-MS, Abbildung S5) verifiziert.…”
unclassified